DAMPAK WABAH FLU BURUNG (Avian influenza) TERHADAP PERMINTAAN DAGING AYAM PEDAGING DI PASAR TRADISIONAL (Studi Kasus di Kota Surakarta) - Ayu Intan Sari; Ginda Sihombing; Sutrisno Hadi Purnomo (Universitas Sebelas Maret, 2010)
The purpose of this research is to analyze achievement elastisity, to know the different level of consument achievement toward meet broiler in early and final month, to know the factors influence meet broiler achievement, and to know the influent of Al occur toward consument favorite on buying meet broiler in traditional market in Surakarta. The step of collecting data of this research was done on Juni to Juli 2007 with the taking data location in Gede market, Legi market, Kleco market and Kadipiro market. The research basic method used is descriptive method with taking sample technic is porposively random sampling on selling respondent is about 40 people. The analysis data used is analysis of double linier product function.The result of this research shows the average of the buying total per day in every selling respondent is about 51,75 broiler. The average detail of the buying consist of in early month is about 52 broiler and in final month is about 51,5 broiler/day/treader. From t-test exam is known that t value count the average month and meet broiler in early month and in final month is same. It means 0,240 where the value smallest than the value t table of the belileve level 95% (t count < t table), so H0 achieved means the buying meet broiler in early and in final month is not different. From regretion analysis result was done achieve regretion model: Y=0,908+0,040X1+0,000X2-0,001X3+0,143X4-0,088X5+e, with determinant coeficient (R2) is about 22,9%. The F value count is about 10,651 where value Fcount > Ftable is about 2,621 with df to counting is about 5 (k-1) and df together independent variable (the income of consument family, the price of meet broiler, the price of substitution goods, the total of members of consument family, and (the total of meet broiler achievement). While, the individually is only price of meet broiler variable has fact influent. From the analysis result conclude that the achievement of meet broiler in Surakarta is inelastically, it caused by significant regretion, coefisien is 0,001 and among value 0 and 1 (0<ES<1).